KINERJA PENDAMPING DALAM MENINGKATKAN PEMBANGUNAN DESA Kajian Pembangunan di Desa Sido Rukun dan Lubuk Bumbun Kecamatan Margo Tabir Kabupaten Merangin Provinsi Jambi - Tahir, M. Irwan; Dwi Sasmi, Yesi Refinalisya (Jurnal Politik Pemerintahan Dharma Praja, 2019)
Companion Performance in Improving Village Development. Development Study in Sido Rukun Village and Lubuk Bumbun Margo Tabir District, Merangin District, Jambi Province. This study aims to describe the performance of Village Facilitators in increasing village development in Sido Rukun Village and Lubuk Bumbun Margo Tabir District, Merangin District, Jambi Province. The research was carried out through direct observation to the field to carry out data collection through interviews and supported literature reference sources related to analyzing data findings. The method used is descriptive qualitative. The researcher is directly involved in extracting information. Data analysis was done deductively by using Mitchell’s theory (1987) as an analysis knife to describe the performance of village facilitators, with indicators of Quality of Work, Promptness, Initiative, Capability, and Communication. The results showed that the performance of village facilitators in improving village development in Sido Rukun and Lubuk Bumbun Villages in Margo Tabir District, Merangin District, Jambi Province, if measured by Mitchell’s performance indicators, was considered quite good.